Crane-powered pectus excavatum repair: the NeoPectus surgery - Park, Hyung Joo; Rim, Gongmin; Yoon, Seung Keun (Frontiers in Surgery, 2023)
The conventional technique for pectus excavatum repair was pushing up the depressed chest wall by turning over the convexity of the bent pectus bar. We developed a new concept that total crane lift was used as the source of power to elevate the depressed sternum without using pectus bar leverage. This study aims to verify the efficacy of exclusively crane-powered pectus excavatum repair during the recent years.Among 3622 pectus deformity repairs since 1999, 691 cases repaired with the total crane power between 2017 to 2022 were enrolled. The mean age was 12.0 years (3-45). The operative technique involved wire/screw crane elevation of the sternum, the entire chest wall remodeling with the cross or parallel bars, the bridge/claw bar fixations, and other adjunctive techniques. Outcome analysis included morphological variations, patterns of pectus bar placement, and complication rates. There was no case of bar displacement.The crane technique and pectoscopy (100%) were used. The bar placements were parallel bar (22.0%), crossbar (47.5%). The bar fixations were the claw fixators for a single bar (30.5%) and the bridge plates for multiple bars (69.5%). The flare-buster and magic strings were liberally used. No serious complications or catastrophic events occurred, but minor complications occurred in 16.9%: pneumothorax in 7.4% (51), pleural effusion in 1.6% (11), and wound problems in 0.4% (3).The crane-powered pectus excavatum repair showed excellent results with minimal complications and no bar displacement. This innovative approach, part of the NeoPectus surgery, represents a significant advancement in correcting pectus excavatum deformities by utilizing a crane machine to elevate the chest wall.